Gender differences in the skill content of jobs - Rita Pető; Balázs Reizer (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2021)
There is significant heterogeneity in actual skill use within occupations even though occupations are differentiated by the tasks workers should perform during work. Using data on 12 countries which are available both in the Programme for the International Assessment of Adult Competencies survey and International Social Survey Program, we show that women use their cognitive skills less than men even within the same occupation. The gap in skill intensity cannot be explained by differences in worker characteristics or in cognitive skills. Instead, we show that living in a partnership significantly increases the skill use of men compared with women. We argue that having a partner affects skill use through time allocation as the gender penalty of partnered women is halved once we control for working hours and hours spent on housework. Finally, we do not find evidence of workplace discrimination against women.
Keywords: J16; J22; J24; 330; Gender Gaps; Time Allocation; Human Capital; Skills